X-Ray Polarization of the BL Lacertae Type Blazar 1ES 0229+200 - Steven R. Ehlert; Ioannis Liodakis; Riccardo Middei; Alan P. Marscher; Fabrizio Tavecchio; Iván Agudo; Pouya M. Kouch; Elina Lindfors; Kari Nilsson; Ioannis Myserlis; Mark Gurwell; Ramprasad Rao; et al. (United States, 2025)
We present polarization measurements in the 2–8 keV band from blazar 1ES 0229+200, the first extreme high synchrotron peaked source to be observed by the Imaging X-ray Polarimetry Explorer (IXPE). Combining two exposures separated by about two weeks, we find the degree of polarization to be ΠX = 17.9% ± 2.8% at an electric-vector position angle ψX = 250 ± 46 using a spectro-polarimetric fit from joint IXPE and XMM-Newton observations. There is no evidence for the polarization degree or angle varying significantly with energy or time on both short timescales (hours) or longer timescales (days). The contemporaneous polarization degree at optical wavelengths was >7× lower, making 1ES 0229+200 the most strongly chromatic blazar yet observed. This high X-ray polarization compared to the optical provides further support that X-ray emission in high-peaked blazars originates in shock-accelerated, energy-stratified electron populations, but is in tension with many recent modeling efforts attempting to reproduce the spectral energy distribution of 1ES 0229+200, which attribute the extremely high energy synchrotron and Compton peaks to Fermi acceleration in the vicinity of strongly turbulent magnetic fields.